Synthesis and Antibacterial Activity of Azomethine Ligand and Their Metal Complexes: A Combined Experimental and Theoretical Study - Khalidah Hamil Manati Al Furaiji; Rehab Abdul Mahdi Al Hassani; Hanaa Hassan Hussein (Universitas Gadjah Mada, 2024)
An asymmetrical Schiff base triazole ligand (4-((3-mercapto-5-(naphthalen-1-ylmethyl)-4H-1,2,4-triazol-4-yl)imino)methyl)methoxy) (L) was used to generate novel micro complexes of Cr(III), VO(IV), and Mn(II) ions. Different spectroscopic techniques, including UV-vis spectroscopy, Fourier transform infrared spectroscopy (FTIR), flame atomic absorption, conductivity tests, CHNS elemental analysis, and magnetic susceptibility, were used to determine the structures of the Schiff base micro complexes. The density functional theory (DFT) calculation was screened to consider selected complexes. The observed data indicated their stability, and the expected chemical formula of vanadium(IV) was square pyramidal geometry in VO(L) complex formula. In contrast, the Cr(III) and Mn(II) complexes have octahedral geometry in the formulas. Frontier molecular orbitals calculations (MO) have also been performed to better understand the nature of orbitals, EHOMO, and ELUMO, allowing us to confirm the experimental finding. Pseudomonas aeruginosa and Bacillus subtilis, two types of potentially dangerous bacteria, were subjected to tests to see whether L and its metal complexes have any antibacterial activities or not. All compounds were also tested for their antifungal activity against two different types of fungi, Penicillium spp. and Aspergillus flavus. There is significant action has been noted in all cases for the complexes.